2016
DOI: 10.1371/journal.pone.0161902
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for Predicting the Prognostic Value of Pre-Therapeutic CA15-3 and CEA Serum Levels in TNBC Patients

Abstract: Previous studies have indicated that carcinoembryonic antigen (CEA) and cancer antigen 15–3 (CA15-3) levels are both independent prognostic factors in breast cancer. However, the utility of CEA and CA15-3 levels as conventional cancer biomarkers in patients with triple-negative breast cancer (TNBC) remains controversial. The current study was performed to explore the predictive value of pre-therapeutic serum CEA and CA15-3 levels, and nomograms were developed including these serum cancer biomarkers to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The value of tumor markers varies depending on the molecular sub-group. To determine the cut-off value with the strongest prognostic ability, several different cut-off values have previously been applied for CEA (2-10 ng/ml) and CA15-3 (21.8-60 U/ml) (12,14,18,(38)(39)(40)(41). In the present study, CEA and CA15-3 were identified as prognostic predictors for young patients with breast cancer according to ROC curve analysis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The value of tumor markers varies depending on the molecular sub-group. To determine the cut-off value with the strongest prognostic ability, several different cut-off values have previously been applied for CEA (2-10 ng/ml) and CA15-3 (21.8-60 U/ml) (12,14,18,(38)(39)(40)(41). In the present study, CEA and CA15-3 were identified as prognostic predictors for young patients with breast cancer according to ROC curve analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Among several tumor markers, CEA and CA15-3 are the two most widely used for breast cancer. Numerous studies have been performed to quantitatively evaluate the serum levels of these two tumor markers, which have identified a wide range of cut-off values for predicting the prognosis of poor survival in breast cancer (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). At present, the predictive abilities of CEA and CA15-3 remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEA is less widely investigated as a prognostic factor than CA15-3 because it has a less positive rate and is more controversial. Some studies have reported that CEA is not a predictor in primary and metastasis breast cancer [ 20 , 21 , 23 , 24 ], but others have reported that high concentrations of CEA were related to a poor prognosis in breast cancer [ 17 , 25 , 26 ]. These above contradictory results of CA15-3 and CEA in breast cancer regarding their prognostic value may be due to small sample sizes, variable study designs, or other biases in each single study.…”
Section: Introductionmentioning
confidence: 99%
“…who carried out a research on serum CA15-3 in different stages of breast cancer. On the contrary, Dai et al, [16] found that CA15-3 was elevated in 7.7%, 20.6%, 35.7% and 63.5% of patients with stage I, II, III, IV breast cancer respectively, (Cut off: 21.8U/ml). This can be explained by the fact that increased concentrations of CA 15-3 may be elevated in patients with benign ovarian cysts, benign breast disease, and benign liver disease.…”
Section: Sensiti Vity and Specificity Of Ca15-3 Cea And Mammaglobin mentioning
confidence: 90%